1970
DOI: 10.1001/jama.1970.03170170066019
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cystic Adenomatoid Malformation With Anasarca

Abstract: Theories of the etiology of prostatic calculi at¬ tempt to account for the effects of a variety of factors including glandular secretions, hormones, aging, infection, and urinary obstruction. Many early writers thought that calculi resulted solely from prostatitis and urinary reflux into prostatic ducts.6 They postulated than an inflammatory exú¬ date initiates encrustation of the corpora amylacae, creating a cycle of infection, stasis, and precipita¬ tion of urinary salts.Contemporary reports minimize influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…If the mass does not communicate freely with the tracheobronchial tree then it may be a source of indolent infection (Halloran et al 1972). The infants tolerate lung resection well (Aslam et al 1970;Halloran et al 1972) but the ultimate outcome depends on the extent of pulmonary hypoplasia and the state of maturation of the normal lung tissue (Donn et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…If the mass does not communicate freely with the tracheobronchial tree then it may be a source of indolent infection (Halloran et al 1972). The infants tolerate lung resection well (Aslam et al 1970;Halloran et al 1972) but the ultimate outcome depends on the extent of pulmonary hypoplasia and the state of maturation of the normal lung tissue (Donn et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…There is a tendency for the cystic mass to expand progressively after birth, leading to air trapping [2]. Immediate surgical decompression is the treatment of choice, and though this has been shown to be well-tolerated [1,2] ultimate survival depends upon both the extent of pulmonary hypoplasia and the state of maturation of the normal lung tissue. Analogous to the emergency presented by diaphragmatic hernia, immediate and proper surgical intervention might salvage many of the affected infants whose lungs would otherwise support life.…”
Section: Discussionmentioning
confidence: 99%
“…There were no other congenital anomalies. has been reported frequently [1,3,5]. Ost6r [5] reported that 80% of affected pregnancies demonstrated acute hydramnios, with the onset usually one to three weeks prior to delivery.…”
Section: Case Reportmentioning
confidence: 99%